Aesthetics and its Jurisprudential Applications in the Holy Qur’an through the Objectives of Sharia’a - Abusoud, Suzan; Alnadaf, Maher (Jordan Journal of Islamic Studies, 2023)
This research attempts to guide generations to the right path of the Holy Qur’an for the sake of grasping its implications and practically applying them. It also tries to delve deep into preserving human natural instinct by enlightening its rational and affectionate capacity via the Holy Qur’an’s instructions as well as abiding by its teachings, especially in light of the spread of interpolation concerning the misconception of values in which we live nowadays. In this respect, this research mainly defines aesthetics and its pertinent aspects inferred from The Holy Qur’an’s employment of its standards and functions. Furthermore, it explores such aesthetics’ contiguous relationship with the objectives of Shari’ah by proving it as one integral principle of Shari’ah, and it deduces inextricable branches of Fiqh from it. The research concludes with several findings, the most important of which is that aesthetics is both abstract and tangible, its manifests are connotative and denotative, it appears in congenital creation and moral manners, and it places the abstract beauty over the tangible one in case of contradiction in accordance with religion, reason, instinct, and conscience.